Pengaruh Ukuran Perusahaan, Struktur Modal Dan Likuiditas Terhadap Profitabilitas Pada Perusahaan Pertambangan Sub Sektor Batu Bara Tahun 2020 – 2023 - Rahmaita Rahmaita; Yudha Agustiyono (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect of Company Size, Capital Structure, and Liquidity on Profitability. This research is a quantitative research. The type of data used is secondary data obtained from https://www.idx.co.id/id and company websites. The population in this study is the Coal Mining Sector companies listed on the Indonesia Stock Exchange in 2020-2023. While the sample of this study was determined using sample statistics, resulting in a total of 119 data points that can be processed. The analytical method used is inferential statistical analysis using SmartPLS 4 software. The results of this study indicate that Company Size has a positive and significant effect on Profitability, Capital Structure has a negative effect on Profitability, Liquidity has a significant effect on Profitability.